Atmospheric sulfur and climate changes : a modelling study at mid and high-southern latitudes. - Castebrunet, Hélène, Hc (HAL CCSD, 2007)
The mid and high-southern latitudes are still marginally affected by anthropogenic sulfur emissions.They are the only regions in the world where the natural cycle of the atmospheric sulfur maystill be observed. Sulfur aerosols are well-known for their radiative impact, and thus interact withclimate. Climate can in turn affect atmospheric sulfur sources, distribution and chemistry. Antarcticice cores provide information on the evolution of climate and sulfur deposition at the surface of theice sheet at glacial-interglacial time scales. The aim of this thesis is to develop and use modelingtowards a better understanding of the atmospheric sulfur cycle in antarctic and sub-antarctic regions.Ice core data are used to validate model results under glacial climate conditions. An AtmosphericGeneral Circulation Model (AGCM) coupled to a sulfur chemistry module is used : the LMD-ZTSulfurmodel, version 4. An update of both the physical and chemical parts of the model. The modelwas first performed. The impact of there changes on modelled sulfur cycle are evaluated for modernclimate. Further, boundary conditions are adapted to simulate the atmospheric circulation and sulfurcycle at the Last Glacial Maximum, approximately 20,000 years ago. In the model, sulfur is foundto be highly sensitive to antarctic sea-ice coverage, which is still poorly known during the ice age.An original dataset of ice-age sea-ice coverage was developed. Its impact on the oceanic emissions ofdimethyl sulfide, main precursor of sulfur aerosols at high-southern latitudes, is discussed. Using thesame oceanic sulfur reservoirs as for present day climate, the model broadly reproduces the glacialdeposits of sulfur aerosols on the Antarctic plateau, suggesting little impact of climate on oceanic sulfurproduction in the Antarctic region. Sensitivity tests were carried out to draw an up-to-date statusof major uncertainties and difficulties facing future progress in understanding atmospheric sulfur andclimate. Les moyennes et hautes latitudes Sud sont les ...